Extracellular Matrix in Aging Aorta - Mammoto, Akiko; Matus, Kienna; Mammoto, Tadanori (Frontiers in Cell and Developmental Biology, 2022)
The aging population is booming all over the world and arterial aging causes various age-associated pathologies such as cardiovascular diseases (CVDs). The aorta is the largest elastic artery, and transforms pulsatile flow generated by left ventricle into steady flow to maintain circulation in distal tissues and organs. Age-associated structural and functional changes in the aortic wall such as dilation, tortuousness, stiffening and losing elasticity hamper stable peripheral circulation, lead to tissue and organ dysfunctions in aged people. The extracellular matrix (ECM) is a three-dimensional network of macromolecules produced by resident cells. The composition and organization of key ECM components determine the structure-function relationships of the aorta and therefore maintaining their homeostasis is critical for a healthy performance. Age-associated remodeling of the ECM structural components, including fragmentation of elastic fibers and excessive deposition and crosslinking of collagens is a hallmark of aging and leads to functional stiffening of aorta. In this mini review, we discuss age-associated alterations of the ECM in the aortic wall and shed light on how understanding the mechanisms of aortic aging can lead to the development of efficient strategy for aortic pathologies and CVDs.